ANALISIS KELAYAKAN USAHATANI PENGGEMUKAN DOMBA SISTEM KANDANG PANGGUNG DI DESA SIDOMULYO KECAMATAN SILO, KABUPATEN JEMBER - Ridho, Atok Ainur; Prawitasari, Saptya (BUANA SAINS, 2023)
The aim of this research was to measure profit, cost efficiency, and profitability of fattening and rearing sheep farming using the stilt system in Sidomulyo Village, Silo District, Jember Regency. This research uses descriptive-analytic and survey methods. The research area is Sidomulyo Village, Silo District. The research object was sheep breeders with a stilt cage system with a total sample of 32 people. The data analysis method used is profit analysis, cost efficiency, and profitability. The results showed that the profit of fattening and rearing sheep farming using the stilt system in Sidomulyo Village, Silo District, Jember Regency was IDR 7,200,200 per 10 heads or an average of IDR 240,000 per month. The efficiency of farming costs for fattening and rearing sheep using the stilt pen system in Sidomulyo Village, Silo District, Jember Regency indicated by an R/C ratio of 1.97. This business is classified as efficient because it is higher than the assumed bank interest rate of 12% /year. The profitability of farming for fattening and rearing sheep using the stilt cage system in Sidomulyo Village, Silo District, Jember Regency was 41.56%. Based on this value, the business of fattening sheep was more profitable than saving money in a bank with an assumed bank interest rate of 12% /year.